2006
DOI: 10.1016/j.rssm.2005.10.001
|View full text |Cite
|
Sign up to set email alerts
|

What we have learned: RC28's contributions to knowledge about social stratification

Abstract: *We thank RC28 members who provided the starting point for this paper at the special session on RC28 accomplishments at the 2002 World Congress of Sociology. We also thank RC28 members who commented on an earlier draft of this paper that was presented at the 2003 RC28 meeting in Tokyo, especially Wout Ultee for his valuable comments at the Tokyo meeting. Finally, we thank Yunus Kaya for constructing a database of presentations at RC28 over the last twenty years, which has facilitated our writing this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
207
1
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(231 citation statements)
references
References 93 publications
7
207
1
16
Order By: Relevance
“…A key interest has revolved around the extent to which social mobility regimes differ between countries at different levels of development or with a different institutional structures, and whether these patterns changed during and after industrialization (see, e.g., Bourdieu, Ferrie and Kesztenbaum 2009;Breen 2008;Erikson and Goldthorpe 1992;Ferrie 2005;Ganzeboom, Luijkx and Treiman 1989;Ganzeboom, Treiman and Ultee 1991;Grusky and Hauser 1984;Hout and DiPrete 2006;Lipset and Bendix 1959;Ferrie 2007, 2013;Treiman 1970;Van Leeuwen and Maas 2010). In turn, these questions are also related to issues of social stratification more generally, and the extent to which these patterns are dependent on economic development (see, e.g., Treiman 1976).…”
Section: Introductionmentioning
confidence: 99%
“…A key interest has revolved around the extent to which social mobility regimes differ between countries at different levels of development or with a different institutional structures, and whether these patterns changed during and after industrialization (see, e.g., Bourdieu, Ferrie and Kesztenbaum 2009;Breen 2008;Erikson and Goldthorpe 1992;Ferrie 2005;Ganzeboom, Luijkx and Treiman 1989;Ganzeboom, Treiman and Ultee 1991;Grusky and Hauser 1984;Hout and DiPrete 2006;Lipset and Bendix 1959;Ferrie 2007, 2013;Treiman 1970;Van Leeuwen and Maas 2010). In turn, these questions are also related to issues of social stratification more generally, and the extent to which these patterns are dependent on economic development (see, e.g., Treiman 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The sociological research showed that for people whose parents have a high occupational status, education functions as a means of guaranteeing high status, but for those whose parents have low status, education is the principal mechanism of upward mobility (Hout & Diprete, 2006). In general, education lessens the direct effect of the parent's status on the child's.…”
Section: Social Mobility: Income Occupation and Educationmentioning
confidence: 99%
“…The general conclusion from decades of research on socioeconomic inheritance suggests that parental resources correlate positively with children's adult educational and socioeconomic outcomes (e.g., Ganzeboom et al 1991;Solon 1999;Hout and DiPrete 2006;Breen and Jonsson 2005). The literature suggests that the positive effects of parental resources are based on either investments that parents are able to make in their children or parental endowments that their children can benefit from (Becker and Tomes 1976;Coleman 1988;Rosenzweig 1990;Musick and Mare 2006;Esping-Andersen 2015).…”
Section: Mechanisms Of Intergenerational Social Inequality At the Indmentioning
confidence: 99%
“…Many countries have moved in this direction; the conclusion of existing research is that socioeconomic inheritance has weakened in most of the developed countries over the period after World War II (Ganzeboom et al 1991;Treiman and Ganzeboom 2000;Hout and DiPrete 2006; for an exception, the United States, see Beller and Hout 2006). Yet parental background continues to play an important role in socioeconomic attainment in all societies.…”
Section: Introductionmentioning
confidence: 99%